Bentuk lokusi, ilokusi, dan perlokusi siswa dalam pembelajaran tematik - Heny Kusuma Widyaningrum; Cahyo Hasanudin (BAHASTRA, 2019)
AbstrakThis study aims (1) to describe localized, illocutionary, and student-speaking acts of speech acts against teachers in thematic learning at Klegen 02 Madiun. The method used is a qualitative descriptive method that leads to a description of the actual conditions in the field and then described in the text. Data collection techniques using interviews, observation, and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this study are 1) locus speech acts in thematic learning conducted by teachers and students as well as students to the teacher is good enough. The intensity is not often on the grounds that children are accustomed to convey something without any other purpose, 2) the acts of students' illocutionary acts of speech occur in the form of assertive, directive, and expressive speech acts, 3) acts of speech acts are performed to influence others.